PENGARUH CITRA MEREK, KUALITAS LAYANAN DAN PERSEPSI NILAI TERHADAP LOYALITAS MEREK MELALUI KEPUASAN PELANGGAN (STUDI PADA PT. ASURANSI ALLIANZ UTAMA CABANG KOTA SEMARANG) - Fil Alam Alif Alfatah, 13.05.51.0151 (Students' Journal of Economic and Management, 2017)
The goals of this research are to examine and analyze the influence of brand image, service quality, and perceived value on customer satisfaction at PT. Asuransi Allianz Utama Branch of Semarang City. And to examine and analyze the influence of customer satisfaction on brand loyalty of PT. Asuransi Allianz Utama branch of Semarang City. The sampling method used purposive sampling with the limit of insurance period more than one year and the number of samples in this study were 150 respondents. The influence between variable is described by using multiple regression analysis. Based on the results of statistical tests on research about the influence of brand image, service quality, and perceived value on brand loyalty through customer satisfaction (empirical study in PT. Asuransi Allianz Utama branch of Semarang City) can be deduced that brand image doesn’t significantly influence on costumer satisfaction of PT. Asuransi Allianz Utama branch of Semarang City, service quality and perceived value does significantly influence on customer satisfaction of PT. Asuransi Allianz Utama branch of Semarang City, and customer satisfaction does significantly influence on brand loyalty of PT. Asuransi Allianz Utama branch of Semarang City.